Cellular and molecular effects of Baccharis dracunculifolia D.C. and Plectranthus barbatus Andrews medicinal plant extracts on retinoid metabolism in the human hepatic stellate cell LX-2 - Da Silva, Caio Mateus [UNESP]; Caetano, Flávio Henrique [UNESP]; Pereira, Franco Dani Campos [UNESP]; Morales, Maria Aparecida Marin [UNESP]; Sakane, Kumiko Koibuchi; Moraes, Karen C. M. [UNESP] (Springer Nature, 2019)
Background: Chronic hepatic diseases are serious problems worldwide, which may lead to the development of fibrosis and eventually cirrhosis. Despite the significant number of people affected by hepatic fibrosis, no effective treatment is available. In the liver, hepatic stellate cells are the major fibrogenic cell type that play a relevant function in chronic liver diseases. Thus, the characterization of components that control the fibrogenesis in the hepatic stellate cells is relevant in supporting the development of innovative therapies to treat and/or control liver fibrosis. The present study investigated the effects of Baccharis dracunculifolia D.C. and Plectranthus barbatus Andrews medicinal plant extracts in LX-2 transdifferentiation. Methods: LX-2 is a human immortalized hepatic stellate cell that can transdifferentiate in vitro from a quiescent-like phenotype to a more proliferative and activated behavior, and it provides a useful platform to assess antifibrotic drugs. Then, the antifibrotic effects of hydroalcoholic extracts of Baccharis dracunculifolia and Plectranthus barbatus medicinal plants on LX-2 were evaluated. Results: The results in our cellular analyses, under the investigated concentrations of the plant extracts, indicate no deleterious effects on LX-2 metabolism, such as toxicity, genotoxicity, or apoptosis. Moreover, the extracts induced changes in actin filament distribution of activated LX-2, despite not affecting the cellular markers of transdifferentiation. Consistent effects in cellular retinoid metabolism were observed, supporting the presumed activity of the plant extracts in hepatic lipids metabolism, which corroborated the traditional knowledge about their uses for liver dysfunction. Conclusion: The combined results suggested a potential hepatoprotective effect of the investigated plant extracts reinforcing their safe use as coadjuvants in treating imbalanced liver lipid metabolism.
Keywords: Biochemical analyses; Hepatoprotection; HSC transdifferentiation; Lipid metabolism; LX-2 cell line; Traditional knowledge